Pengembangan Media Pembelajaran Fisika Berbentuk Permainan Ular Tangga Menggunakan Adobe Flash untuk Siswa SMP (UPEJ Unnes Physics Education Journal, 2020)
This research aims to develop learning media in the form of snakes and ladder games based on Adobe Flash CS6 and to know the feasibility of the developed media and to know the influence of media use on student learning outcomes. This research was conducted at SMP 23 Semarang in January 2020. The method used is development research method or R&D. The research sample is a grade VII B student at SMP 23 Semarang which consists of 32 students. The results of the due diligence by experts showed that the media deserved to be used as a support for the learning process and there was an increase in learning outcomes in students marked by an increase in N-gain grades.